An Herbal Formula CGplus Ameliorates Stress-Induced Hepatic Injury in a BALB/c Mouse Model - Kim, Hyeong-Geug; Kim, Yun-Hee; Lee, Sung-Bae; Lee, Jin-Seok; Chae, Sung-Wook; Kim, Dong-Gu; Son, Chang-Gue (Frontiers in Pharmacology, 2020)
Introduction: Stress is a well-known factor for inflammation in diverse organs/tissues. Stress also leads to liver injury, which was supported by clinical observations and animal studies. We herein investigated the hepatoprotective property of an herbal formula (called as CGplus) consisting of Artemisia iwayomogi, Amomum xanthioides, and Salvia miltiorrhiza against stress-induced hepatic damage. Methods: Male BALB/c mice were orally administered water extract of CGplus (0, 50, 100, or 200 mg/kg) daily for 5 days, and then subjected to immobilization stress for 6 hours on the 5th day. Results: Acute immobilization stress elevated remarkably serum concentrations of stress hormones (corticosterone and adrenaline) and two hepatic injury parameters (ALT and AST), whilethese alterations were significantly attenuated by the administration of CGplus. The increases of oxidative parameters (ROS, NO, lipid peroxidation, and protein carbonyl) and deviation of IL-1β and IL-10 in opposite directions in hepatic tissueswere significantly normalized by CGplus. Pre-treatment with CGplus also notably ameliorated the abnormal activation of toll-like receptor 4 (TLR4), CD14 and lipopolysaccharide-binding protein (LPB) as well as infiltration of neutrophils in hepatic tissues. Conclusion: These results suggest that an herbal formula (CGplus) derived from traditional pharmaceutical theory has a potent protective effect against stress-induced hepatic injury via regulation of pro- (IL-1β) and anti-inflammatory (IL-10) cytokines.